The Political Economy of WikiLeaks: Power 2.0? Surveillance 2.0? Criticism 2.0? Alternative Media 2.0? - Fuchs, Christian (Global Media Journal – Australian Edition: Contribution to the Special Issue on “WikiLeaks: Journalism and the 21st Century Mediascape“ (edited by Hart Cohen and Antonio Castillo))

An Alternative View of Privacy on Facebook - Fuchs, Christian (Information: [special issue on “Trust and privacy in our networked world“, edited by Dieter M. Arnold and Herman T. Tavani])

Web 2.0, Prosumption, and Surveillance. [special issue on “Marketing, consumption and surveillance”, edited by Jason Pridmore and Detlev Zwick] - Fuchs, Christian (Surveillance & Society)

Towards an Alternative Concept of Privacy - Fuchs, Christian (Journal of Information, Communication and Ethics in Society)

A Contribution to the Critique of the Political Economy of Google - Fuchs, Christian (Fast Capitalism)

The Contemporary World Wide Web: Social Medium or New Space of Accumulation? - Fuchs, Christian (The Political Economies of Media. The Transformation of the Global Media Industries)

Cognitive Capitalism or Informational Capitalism? The Role of Class in the Information Economy - Fuchs, Christian (Cognitive Capitalism, Education and Digital Labor)

Two New Critical Internet Studies-Books: Marcus Breen’s “Uprising” and Eran Fisher’s “Media and New Capitalism in the Digital Age” - Fuchs, Christian (tripleC – Journal for a Global Sustainable Information Society)

Critical Media and Communication Studies Today. A Conversation - Fuchs, Christian; Winseck, Dwayne (tripleC)

"BlackBerry-Riots": Gewalt hat andere Gründe [“BlackBerry-Tiots“: Violence has Other Causes“] - Fuchs, Christian (Futurezone)

“Twitter Mobs“ and the Structural Violence of Neoliberalism - Fuchs, Christian (Counterfire)

Review of “The problem of order in the global age. Systems and mechanisms“ (Andreas Pickel) - Fuchs, Christian (Philosophy of the Social Sciences)

‚Grundlegende Betrachtungen zur Technik – Technomorphologische Analysen des Textilen’ - Kraft, Kerstin

‚Glamour und Grauen. Das Erforschen und Ausstellen von Bekleidung aus den 1930er und 1940er Jahren’ - Kraft, Kerstin

Cutting Patterns - Kraft, Kerstin

Photoluminescence Properties of Ordered Mesoporous ZnO - Chernikov, Alexej; Horst, Swantje; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (The Journal of Physical Chemistry C)
Nanoporous ZnO powders with high surface-to-mass ratios (SMR) between 15 and 70 m2 g−1 are synthesized, structurally characterized, and studied by time-resolved photoluminescence (PL). A strong dependence of the recombination dynamics and spectral width on SMR is observed at T = 10 K, and pronounced disorder-induced effects are found in the temperature dependence. Both the thermally induced shift of the PL maximum and the spectrally integrated PL intensity are interpreted by appropriate theoretical models. This consistent quantitative analysis of the experimental data yields a characteristic energy of 15 meV for the disorder scale in the nanoporous ZnO sample with an intermediate SMR.

Analysis of Existing Empirical Research Methods for Studying (Online) Privacy and Surveillance - Sevignani, Sebastian; Kreilinger, Verena; Allmer, Thomas; Fuchs, Christian

Towards a Critical Theory of Surveillance Studies - Allmer, Thomas

Critical Surveillance Studies in the Information Society - Allmer, Thomas (tripleC)

Bildung MACHT Gesellschaft